Experiencing Liminality: An Educational Perspective. (2nd January 2020) - Barrow, Giles; Shaw, Kate; Harvey, Caroline; Hardy, Arabella; Kelly, Amy; Bodenham, Judith
Abstract: The authors explore the educational potential of liminality. Drawing on their individual and collective experience of liminality as part of a personal development program, the group members use a series of journal reflections to illuminate its key features. They suggest that the concept provides rich possibilities for generating transformational educational experiences. Transactional analysis models, including the vulnerability quotient and the educational adaptation of the cycle of development, are used to extend understanding and application of the concept of liminality in relation to the educational field. The article is authored by a collective that comprises both educator and students, and phenomenological experience is prioritized as a way to illuminate theoretical explanation. This latter feature is discussed and raises questions about the interplay between subjective and objective perspectives.